Forty years of temporal analysis of products. Issue 12 (23rd May 2017) - Morgan, K.; Maguire, N.; Fushimi, R.; Gleaves, J. T.; Goguet, A.; Harold, M. P.; Kondratenko, E. V.; Menon, U.; Schuurman, Y.; Yablonsky, G. S.
Abstract : A detailed understanding of reaction mechanisms and kinetics is required in order to develop and optimize catalysts and catalytic processes. Temporal analysis of products (TAP) is an instrument capable of providing such understanding. Abstract : A detailed understanding of reaction mechanisms and kinetics is required in order to develop and optimize catalysts and catalytic processes. While steady-state investigations are known to give a global view of the catalytic system, transient studies are invaluable since they can provide more comprehensive insight into elementary steps. For almost forty years temporal analysis of products (TAP) has been successfully utilized for transient studies of gas phase heterogeneous reactions, and there have been a number of advances in instrumentation and numerical modeling methods in that time. Since TAP is a complex methodology it is often viewed as a niche specialty. With the purpose to make TAP more relevant and approachable to a wider segment of the catalytic research community, part of the intention of this work is to highlight the significant contributions TAP has made to elucidating mechanistic and kinetic aspects of complex, multi-step heterogeneous reactions. With this in mind, an outlook is also disclosed for the technique in terms of what is needed to revitalize the field and make it more applicable to the recent advances in catalyst characterization ( e.g. operando modes).